Decolonising higher education: Black and Minority Ethnic students' experiences at an elite British university. Issue 3 (4th May 2023) - Sakata, Nozomi; Winston-Proctor, Cynthia E.; Harris, Lasana T.
ABSTRACT: Recent movements to decolonise the university have challenged the ideological and political position of authority, reflecting the power relations between different societal groups. Framed by postcolonial and decolonial perspectives, this paper attempts to represent the experiences, values and viewpoints of Black and Minority Ethnic (BME) students at an elite British university who speak for themselves about their lived realities at the institution. Semi-structured interviews and focus group discussions with seven undergraduate and two postgraduate students explored their university experience, academic success, sense of belonging, discrimination and racism. The findings revealed that the students lacked a sense of belonging at the university. Among the factors that undermined this are the predominantly White faculty bodies, exclusive curriculum representation and inter-group interactions divided by racial groups. Cultivating an inclusive university experience will allow BME students to feel a sense of belonging and integrate the racial and ethnic cultural diversity that they represent.